MAGNITIVE: Effectiveness and Feasibility of a Cognitive Training Program Through Magic Tricks for Children With Attention Deficit and Hyperactivity Disorder. A Second Clinical Trial in Community Settings - Bonete, Saray; Osuna, Ángela; Molinero, Clara; García-Font, Inmaculada (Frontiers in Psychology, 2021)
Some studies explored the impact of magic tricks on different basic cognitive processes yet there is a need of examining effectiveness of a cognitive training program through magic tricks for children with ADHD. The present study examines the effectiveness and feasibility of the MAGNITIVE program, a manualized intervention for cognitive training through the learning of magic tricks. A total of 11 children with ADHD (from 8 to 12 years) participated in separated groups of two different community settings (hospital center and school), and were assessed at Pre-treatment, Post-treatment and a 3-months later follow-up in different tasks involving processing speed, sustained attention, selective attention, and mental flexibility. Using non parametric statistical analyses and Reliable Change Index, the results showed that these children receiving MAGNITIVE particularly improved their performance in sustained attention, shifting attention and mental flexibility, changes were also observed in processing speed performance yet further research is needed in terms of selective attention and inhibition, given the great individual differences within this sample. Changes were maintained when the program was finished. In terms of viability, the study proved a good treatment integrity in different contexts (hospital and school setting), adherence to the curriculum (attendance and some practice at home) and high levels of engagement satisfaction. In this second clinical trial, MAGNITIVE program appears to be a feasible training program for children with ADHD, as an alternative for medication when possible.